Chitosan-cellulose particles as delivery vehicles for limonene fragrance - Lopes, Sofia (2018)
This study proposes the use of chitosan-cellulose particles to encapsulate limonene, a fragrant component widely used in the flavor and fragrance industries. As cellulose possesses a stiff molecular structure due to the threedimensional arrangement of hydrogen bonded hydroxyls, its dissolution is difficult to achieve. To surpass this constraint, and solubilize cellulose, LiOH/urea/water systems were tested using different freezing temperatures and number of freezing/thawing/stirring cycles. Then, chitosan-cellulose composite particles were produced and characterized by Scanning Electron Microscopy (SEM) to assess morphology and size, and by Fourier Transform Infrared Spectroscopy (FTIR) and Thermogravimetric Analysis (TGA) to access chitosan-cellulose molecular interactions. The release behaviour of limonene from the chitosan-cellulose particles was studied by gas chromatography (GC). The obtained particles presented an average diameter ranging from 1 to 2mm and spherical shape, characteristics very similar to the corresponding empty cellulose-chitosan composite particles. A good affinity was found between the two biopolymers, cellulose and chitosan. The achieved encapsulation efficiency of limonene was 51.29%, and the produced particles demonstrated a burst release of limonene in the first 24 h, followed by a decrease over 162 h. Based on the achieved results this system seems favourable for applications requiring preservation of sensory qualities and prolonged release of fragrances.